2017
DOI: 10.1007/s12603-016-0792-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between breakfast skipping and obesity among elderly: Cross-sectional analysis of the HEIJO-KYO study

Abstract: Breakfast skipping was significantly associated with obesity among elderly. Poor diet quality and physical inactivity may be potential intermediators underlying the association between breakfast skipping and obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 27 publications
7
29
0
Order By: Relevance
“…The relationship between breakfast skipping and high body mass index (BMI) has been widely reported in adolescent populations in Europe (9), Hong Kong (10), and Fiji (girls) (11). Similar associations were reported in the adult (12), middle-aged adult (13), and elderly (14) populations. Many studies reported that metabolic outcomes were associated with breakfast skipping; however, more evidence is required.…”
Section: Introductionsupporting
confidence: 84%
“…The relationship between breakfast skipping and high body mass index (BMI) has been widely reported in adolescent populations in Europe (9), Hong Kong (10), and Fiji (girls) (11). Similar associations were reported in the adult (12), middle-aged adult (13), and elderly (14) populations. Many studies reported that metabolic outcomes were associated with breakfast skipping; however, more evidence is required.…”
Section: Introductionsupporting
confidence: 84%
“…This finding, based on a cross-sectional study but using a sophisticated measurement, is in agreement with the previous report that omission of the breakfast may induce a resistance to insulin [1]. It suggests that the impairment in insulin sensitivity experimentally found in an interventional study in healthy women becomes important enough in obese subjects to be detected in a cross-sectional study, and that this effect actually associates a decrease in SI and an incomplete adaptation of insulin release to this reduction in SI, resulting in turn in a decrease in glucose tolerance.…”
Section: Discussionsupporting
confidence: 93%
“…It becomes more and more usual in westernized societies to skip the breakfast. Although one could think it is a good idea, since it can decrease the total daily caloric intake, there is a host of epidemiological reports suggesting that this habit is rather associated with a higher prevalence of obesity [1][2][3][4]. In a longitudinal cohort study it can be evidenced that skipping breakfast is associated with weight gain [5].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of shift work, previous human epidemiological studies indicated that shift work, especially the duration of shift work, is associated with an increased risk of obesity [26,27]. Regarding the timing of meals, studies showed that skipping the first meal of the day (breakfast) increases the risk of obesity [28,29], that the multivariable-adjusted odds ratio of obesity was even higher with a late dinner and bedtime snack than with skipping breakfast [30], and that subjects given 2000 calories in a single daily meal for a week showed greater body weight loss when this meal was given at breakfast rather than at dinner [31]. Shift work and varying meal timings not only are associated with the increased risk of obesity but also alter the biological rhythm.…”
Section: Circadian Rhythm In Obesitymentioning
confidence: 99%